Quality of Life of Preschool-Age Children with Thalassemia Major - Nurhidayah, Ikeu (Pediomaternal Nursing Journal, 2022)
Introduction: Health problems caused by thalassemia disease process and treatment affect patients who suffer from this disease, including pediatric patients who are in their preschool age. These problems can interfere with the child's physical, emotional, social, and school functions. This study aimed to describe the quality of life of preschool-age children with thalassemia major in Sumedang and Garut areas. Methods: In this study, a quantitative descriptive design was applied to a sample of 63 parents of children with 3-6 years old children with thalassemia who were recruited using the total sampling approach. The quality of life as a variable was measured using the PedsQLTM 4.0 Generic Core Scales for parent-proxy reports. Data collected were then analyzed for the mean score and categorized into good or poor quality of life, which were then expressed in frequencies and percentages. Results: Results showed that the mean score of quality of life was 75.94, with the mean scores for physical function, emotional function, social function, and school function of 75.79, 71.98, 87.46, and 60.95, respectively. The majority of preschool-age children with thalassemia have poor quality of life. The dimension that receives the most negative influence is the school function. Conculusion: It is suggested that nurses can improve the quality of life of these children by identifying the impaired functions and providing the appropriate care, such as facilitating the needs of these children to receive blood transfusions in hospitals.